Aerobic sludge granulation: state-of-the-art. (21st July 2009) - Campos, Jose Luis; Figueroa, Monica; Mosquera-Corral, Anuska; Mendez, Ramon
Recently, the research focused on the development and operation of aerobic granular biomass has increased in interest, due to the advantages of this option as compared to the conventional activated sludge systems traditionally used for the biological treatment of wastewater. The aerobic granular sludge is produced in Sequential Batch Reactors (SBR) where a large amount of biomass is accumulated by means of the improvement of its settling properties. These compact systems allow the reduction of the required space for implantation and favour the treatment of large loads of contaminants and the performance of the nitrification and denitrification processes simultaneously.